Adsorption and Micellization of Gemini Surfactants with Diethylammonium Headgroups: Effect of the Spacer Rigidity. Issue 4 (4th May 2017) - Liu, Zhitian; Ge, Yifan; Zhang, Qi; Gao, Xiang; Cai, Xiong; Chen, Mengyao; Yu, Xuechen
Abstract : Abstract: A series of novel cationic gemini surfactants p ‐phenylenedimethylene bis(alkyldiethylammonium) chloride (abbreviated as G m, m is the carbon numbers of hydrophobic tails) were synthesized. Their surface properties and aggregation behavior were investigated by surface tension, electrical conductivity, steady‐state fluorescence, dynamic light scattering and transmission electron microscopy measurements, and compared with gemini surfactants with a flexible hexanediyl spacer and diethylammonium headgroups [abbreviated as C m C 6 C m (Et)]. It was found that G m reached adsorption equilibrium at the air–water interface at the critical micelle concentration, but C m C 6 C m (Et) did not. The packing densities and the aggregation surface charge densities of G m are less than that of C m C 6 C m (Et). Pre‐micellar association occurs in aqueous solutions of gemini surfactants with m ≥ 14. The ability to form pre‐micellar aggregates increases with increasing the length of alkyl chain. Gemini surfactants with rigid p ‐xylylene spacer are more prone to form the pre‐micellar aggregates. The rigidity of the spacer of gemini surfactants has little effect on the aggregation micropolarity sensed by pyrene. Only vesicles were found in aqueous solutions of these gemini surfactants, and G m with p ‐xylylene spacer tends to form larger vesicles which have loose structures with low surface charge density.